Some Issues Related To Cash Flow Statement in Accounting Education: The Case of Turkey - Can Ozturk (Journal of Accounting and Management Information Systems (JAMIS), 2015)
This paper focuses on some issues related to the cash flow statement in the context of accounting education in Turkey. I identify eight aspects related to the cash flow statement based on my experience in teaching IAS 7 Statement of Cash Flows, and discuss their evolution over time. The paper also incorporates the educational perspective of Turkish accounting academics who teach an undergraduate level accounting course that covers this statement. For the purpose of this study, a survey of Turkish academics was conducted. The findings provide insights on how the students' competencies related to the cash flow statement should be improved in the context of undergraduate level accounting education in Turkey and, by extension, in Central and Eastern European countries. While the paper is focused on the Turkish context, the findings might be of interest for other countries in the region, embarked in the modernization of financial reporting and International Financial Reporting Standards-based accounting education.
Keywords: M41; M49; 650; cash flow statement; accounting higher education; Turkey